Investigating a Paradigm Shift in Investment Pattern of Working Women of Haryana - Kumar, Narender; Sofat, Dr. Rajni (The journal of contemporary issues in business and government, 2023)
This study airs into the changing investment habits of Haryana's working women. To do so, a sample size of 300 employed females has been chosen from the six top universities identified by NIRF ranking. T-test has been employed to study the investment trends of Haryana's working women. For this purpose, 3 public &private universities and 3 public & private banks with higher RBI earnings in 2020 were selected. The women working in different sectors of Haryana were given a standardized questionnaire. The study's findings supported that a paradigm shift in investment patterns has been found in all investment avenues. The findings of the study are ice breaking for financial advisors and consultants, as it shifts the investment pattern of working women. This change in preference requires them to update their strategies accordingly. Working women are increasingly becoming independent in financial decisions, creating an opportunity for financial services to tailor their marketing plans to increase investor engagement.